Study on clinically manifested reproductive health problems of dairy cows managed under intensive and semi-intensive production systems in Wondo Genet district, Southern Ethiopia - Amene Fekadu; Yifat Denbarga; Tesfaye Belay; Desie Sheferaw; Fufa Abunna; Kebede Amenu; Rahmeto Abebe; Mesele Abera; Berhanu Mekibib (East African Journal of Biophysical and Computational Sciences)
Reproductive disorders in cows are crucial as reproduction and fertility are the two key pillars of dairy production profitability. The study was conducted to identify and estimate the prevalence of clinically manifested postpartum reproductive disorders, to identify the associated risk factors and to estimate the sero-prevalence of brucellosis in dairy cows kept under intensive and semi-intensive dairy farms in Wondo Genet district from November 2019 to September 2020. Out of the total 205 cows examined, 90 cows (43.90%) had at least one of the reproductive problems identified by either questionnaire interview or regular follow up of individual cows. Out of 146 cows retrospectively and 59 cows prospectively assessed for the presence of any reproductive disorder, 62 (42.47%) and 28 (47.46%) cows had at least one reproductive disorders, respectively. Retained fetal membrane, abortion, uterine infections, anestrous and repeat breeding are the major reproductive disorders encountered followed by dystocia, milk fever and prolapses of the vagina and/or uterus. Among the considered host and management related risk factors, only presence of previous reproductive disorder had statistically significant association with the occurrence of reproductive disorder (p<0.05). This study also demonstrated that none of the serum samples collected from Wondo Genet and other towns (namely Hawassa, Wolaita Sodo and Arsi Negelle) and tested using Indirect Multi-species ELISA was positive for bovine brucellosis. Further studies, preferably laboratory based, should be conducted to identify the underlined causes of these problems in different parts of the country. Meanwhile, awareness should be created to farm owners/attendants to improve their farm management system.